C02 CORROSION IN OIL AND GAS PIPELINES (Mechanistic Modelling) - WAN ISMAIL, WAN AHMAD ZIKRI (Universiti Teknologi PETRONAS, 2010)
Existence of C02, a corrosive gas with production is one of major obstacles that faced by oil and gas industry. C02 will react will water to form weak carbonic acid which later react with metal. Corrosion is process where electrochemical process takes place in the presence of electrolytes and corrosive agents in all metal equipments including oil and gas pipelines. There are several key factors that affect the process of corrosion including temperature, pH, C02 partial pressure, the effect of flow, corrosion inhibitor, organic acid, glycol/methanol, condensation in wet gas flow and non-ideal solution & gases [1 0]. In oil and gas business, any decision made is carefully decided as it involves money and cost. As well as selecting equipments for operation purpose, all factors including price, availability and lifespan of the product should be taken into consideration to make sure the profit of the project is maximized. Since C02 corrosion is one of the factors that contribute in shortening the lifespan of equipments especially for oil and gas pipelines, one efficient method should be used to estimate the corrosion rate by considering all causes of C02 corrosion. Mechanistic model is an effort in predicting the corrosion rate of C02 corrosion of mild steel. In this project, one prediction model is run based on a model developed by Corrosion in Multiphase System Center of Ohio University. This model takes temperature, pressure, C02, water chemistry, pipe as major input calculating corrosion rate [5]. Prediction model is used to evaluate C02 corrosion rate of carbon steel for pipelines in oil and gas industry